World synopsis of described species of the genus Platypygus Loew (Diptera: Mythicomyiidae: Platypyginae) - Gharali, Babak; Evenhuis, Neal L.; Almeida, Jorge (Zootaxa, 2013)
The taxonomy of the genus Platypygus Loew is summarized, previously described species are reviewed based on examination of types, and a key to known species of the genus worldwide is presented. All previously described species are diagnosed and illustrated. The male genitalia of P. ridibundus (Costa) and female genitalia of P. americanus Melander are described for the first time. Some characters supporting the monophyly of the genus Platypygus are discussed and the Nearctic Cyrtisiopsis americanus (Melander) is restored to its original combination as Platypygus americanus. The type status of Platypygus bellus Loew, P. lativentris Loew, P. pumilio Loew, and P. turkmenorum Paramonov is clarified and a lectotype is selected for Platypygus kurdorum Paramonov and P. tauricus Paramonov. New country records are given for the following species: P. bellus (Greece); P. chrysanthemi (Israel, Jordan); P. kurdorum (Israel, Jordan, Syria); P. limatus (Nepal, Thailand); P. pumilio (Greece, Turkmenistan); P. ridibundus (Cyprus, Israel, Portugal), P. titanomedea (Jordan, Turkey).